Pengembangan "Perasaan Kita" sebagai Upaya Internalisasi Empati pada Siswa SMP - Muharammah, Nanda Widya; Setiyowati, Arbin Janu; Flurentin, Elia (Buletin Konseling Inovatif, 2025)
One of the factors that cause cases of aggression that occur among adolescents is the low level of individual empathy. This research and development aim to develop the "Perasaan Kita" media as a student tool in the internalization of empathy. "Perasaan Kita" is a media in interactive books by utilizing the QR code feature in its use. A guidebook for school counselors also accompanies this media to provide essential services in schools. The research method used is research and development using the Borg and Gall model, adapted according to the situation and field conditions. Test material experts, media experts, and potential users evaluate the acceptance of the developed media by looking at accuracy, usability, and convenience. The research instrument uses an expert and prospective user assessment format. The material and media expert test results were then analyzed using the analysis of the inter-rater agreement model, while the results of the prospective user test were analyzed using the numerical average. The test results show that the "Perasaan Kita" media gets a high score, so it can be interpreted that the "Perasaan Kita" media is an appropriate medium used by junior high school students to internalize empathy.